Assessment of knowledge of skin cancer prevention and its relation with sun exposure and photo protection amongst gym academy members on the south of Santa Catarina, Brazil Avaliação do conhecimento quanto à prevenção do câncer de pele e sua relação com os hábitos da exposição solar e fotoproteção em praticantes de academia de ginástica do sul de Santa Catarina, Brasil - Mariana Rocha Fabris; Edson Souza Machado Durães; Beatriz Castellar de Faria Martignago; Luiz Felipe de Oliveira Blanco; Thiago Rocha Fabris (Sociedade Brasileira de Dermatologia, 2012)
BACKGROUND: Skin cancer is the most frequent neoplasia in several parts of the world and also in Brazil. There is evidence of an increase in morbidity and mortality from skin cancer. Although the incidence of skin cancer is increasing, it is estimated that 45% of all preventable cancers worldwide are skin neoplasias. Several studies have emphasized the need for campaigns to encourage sun protection. OBJECTIVE: To assess the knowledge about skin cancer prevention and its association with sun exposure and photo protection in gym members. METHODS: We conducted a cross-sectional, descriptive and quantitative study during January to July 2009, including gym members of both sexes in the city of Criciuma. A self-administered questionnaire was used. The statistical analysis was conducted in a descriptive way in regards to the absolute and relative frequencies of the variables under study. RESULTS: Of the 317 questionnaires studied, 62% were from women and 38% from men. Skin types II and III predominated, and the average age was 27.6 years. 94.3% of the participants reported that they had heard about the risks of sun exposure, mostly in terms of skin cancer risk (80.8%). Most participants, especially women, reported some form of sun protective measure. CONCLUSION: The population studied, similar to that in other regions of Brazil and the world, is aware of the risks of excessive sun exposure and skin cancer prevention, but has not yet incorporated appropriate sun protection measures into their daily habits. FUNDAMENTOS: O câncer da pele é a neoplasia de maior incidência em várias partes do mundo e também no Brasil. Há evidências de aumento da morbidade e mortalidade por câncer da pele. Embora a incidência do câncer da pele esteja aumentando, há estimativas de que em todo o mundo 45% dos cânceres passíveis de prevenção sejam cutâneos. Diversos estudos têm enfatizado a necessidade de campanhas de incentivo à fotoproteção. OBJETIVO: Avaliar o conhecimento quanto à prevenção do câncer da pele e relacioná-lo com os hábitos da exposição solar e fotoproteção em praticantes de academias de ginástica. MÉTODOS: Foi realizado um estudo transversal, descritivo e quantitativo durante o ano de 2009, incluindo praticantes de academias de ginástica em Criciúma, SC, por meio de um questionário autoaplicável. A análise estatística foi realizada de forma descritiva das frequências absolutas e relativas das variáveis em estudo. RESULTADOS: Dos 317 entrevistados, 62% eram do sexo feminino. Prevaleceram os fototipos III e II, e a média de idade foi de 27,6 anos. 94,3% dos entrevistados referiram já ter ouvido falar sobre os riscos da exposição solar, sendo o câncer da pele o mais citado (80,8%). A maior parte das pessoas confirmou o uso de alguma medida de fotoproteção, sendo a maioria delas mulheres. CONCLUSÃO: A população estudada, assim como em outras regiões do Brasil e do mundo, tem noção dos riscos da exposição solar excessiva e das medidas preventivas para o câncer da pele, porém ainda não inseriu em seus hábitos as medidas de fotoproteção de forma adequada.